Curcumin rescues Caenorhabditis elegans from a Burkholderia pseudomallei infection - Eng, Su-Anne; Nathan, Sheila (Frontiers in Microbiology, 2015)
The tropical pathogen Burkholderia pseudomallei requires long-term parenteral antimicrobial treatment to eradicate the pathogen from an infected patient. However, the development of antibiotic resistance is emerging as a threat to this form of treatment. To meet the need for alternative therapeutics, we proposed a screen of natural products for compounds that do not kill the pathogen, but in turn, abrogate bacterial virulence. We suggest that the use of molecules or compounds that are non-bactericidal (bacteriostatic) will reduce or abolish the development of resistance by the pathogen. In this study, we adopted the established Caenorhabditis elegans-B. pseudomallei infection model to screen a collection of natural products for any that are able to extend the survival of B. pseudomallei infected worms. Of the 42 natural products screened, only curcumin significantly improved worm survival following infection whilst not affecting bacterial growth. This suggested that curcumin promoted B. pseudomallei-infected worm survival independent of pathogen killing. To validate that the protective effect of curcumin was directed towards the pathogen, bacteria were treated with curcumin prior to infection. Worms fed with curcumin-treated bacteria survived with a significantly extended mean-time-to-death (p<0.0001) compared to the untreated control. In in vitro assays, curcumin reduced the activity of known virulence factors (lipase and protease) and biofilm formation. To determine if other bacterial genes were also regulated in the presence of curcumin, a genome-wide transcriptome analysis was performed on curcumin-treated pathogen. A number of genes involved in iron acquisition and transport as well as genes encoding hypothetical proteins were induced in the presence of curcumin. Thus, we propose that curcumin may attenuate B. pseudomallei by modulating the expression of a number of bacterial proteins including lipase and protease as well as biofilm formation whilst concomitant